The effect of growth hormone replacement on the thyroid axis in patients with hypopituitarism: in vivo and ex vivo studies. (19th December 2016) - Glynn, Nigel; Kenny, Helena; Quisenberry, Leah; Halsall, David J.; Cook, Paul; Kyaw Tun, Tommy; McDermott, John H.; Smith, Diarmuid; Thompson, Christopher J.; O'Gorman, Donal J.; Boelen, Anita; Lado‐Abeal, Joaquin; et al.
Summary: Objective: Alterations in the hypothalamic–pituitary–thyroid axis have been reported following growth hormone (GH) replacement. The aim was to examine the relationship between changes in serum concentration of thyroid hormones and deiodinase activity in subcutaneous adipose tissue, before and after GH replacement. Design: A prospective, observational study of patients receiving GH replacement as part of routine clinical care. Patients: Twenty adult hypopituitary men. Measurements: Serum TSH, thyroid hormones – free and total thyroxine (T4) and triiodothyronine (T3) and reverse T3, thyroglobulin and thyroid‐binding globulin (TBG) levels were measured before and after GH substitution. Changes in serum hormone levels were compared to the activity of deiodinase isoenzymes (DIO1, DIO2 and DIO3) in subcutaneous adipose tissue. Results: The mean daily dose of growth hormone (GH) was 0·34 ± 0·11 mg (range 0·15–0·5 mg). Following GH replacement, mean free T4 levels declined (−1·09 ± 1·99 pmol/l, P = 0·02). Reverse T3 levels also fell (−3·44 ± 1·42 ng/dl, P = 0·03) and free T3 levels increased significantly (+0·34 ± 0·15 pmol/l, P = 0·03). In subcutaneous fat, DIO2 enzyme activity declined; DIO1 and DIO3 activities remained unchanged following GH substitution. Serum TSH, thyroglobulin and TBG levels were unaltered by GH therapy. Conclusions: In vitro analysis of subcutaneous adipose tissue from hypopituitary human subjects demonstrates that GH replacement is associated with significant changes in deiodinase isoenzyme activity. However, the observed variation in enzyme activity does not explain the changes in the circulating concentration of thyroid hormones induced by GH replacement. It is possible that deiodinase isoenzymes are differentially regulated by GH in other tissues including liver and muscle.